Analisis Faktor Individu dalam mengatasi Technostress pada Karyawan - Alma Nissa Salsabila; Diah Priharsari; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The stress of technology or commonly called technostress is a form of stress when doing a job that links to a technology that can trigger stress. There are individual factors that can rise over technostress, which are mindfulness and self-cation. This technostress is usually within the employees' scope, where employees feel that abilities are not comparable to the technology used and therefore take more time to study the technology. So researchers aim to share new insights with the organization's managers in coping with the technostress negative effects on employees generated by technology use. The study, which also provides insight/prevention for employees to keep their technology in check, thus reducing the incidence of technostress in employees. The data collection technique performed on the application is using a questionnaire spread through social media. The population in this study is working employees of an organization that finishes its job using technology and samples used by 324. Data collection took place for two weeks starting on October 18, 2021. The data that had been collected was prepared to see if it was valid and reliable, after which it was analyzed. The point of this study is that mindfulness and self- cation affects overcoming technostress,